Sclerostin: Current Knowledge and Future Perspectives - Moester, M. J. C. (Springer-Verlag, 2010)
In recent years study of rare human bone disorders has led to the identification of important signaling pathways that regulate bone formation. Such diseases include the bone sclerosing dysplasias sclerosteosis and van Buchem disease, which are due to deficiency of sclerostin, a protein secreted by osteocytes that inhibits bone formation by osteoblasts. The restricted expression pattern of sclerostin in the skeleton and the exclusive bone phenotype of good quality of patients with sclerosteosis and van Buchem disease provide the basis for the design of therapeutics that stimulate bone formation. We review here current knowledge of the regulation of the expression and formation of sclerostin, its mechanism of action, and its potential as a bone-building treatment for patients with osteoporosis.